STUDY OF THE MECHANISM OF VOLTAGE GENERATION IN THE ORDER OF 12-24 V POTENTIAL BY MEANS OF THERMO EMF BASED ON THE SEEBECK EFFECT - U. U. Iskandarov; N. U. Iskandarov (American Journals Publishing, 2025)
This article studies the mechanism of generating potential difference in the range of 12-24 V DC using the thermoelectromotive force arising at the boundary of two dissimilar conductors. The experimental conditions are considered, including the choice of materials, temperature conditions, the influence of the conductor cross-section, and the use of transformers to increase the output voltage. An analysis of the feasibility of this economic approach is carried out, taking into account some costs.
Keywords: Thermoelectric driving force, voltage converters, thermocouple, temperature differential, Seebeck coefficient, virtual circuit, energy consumption, Fermi level, alternative material.